The Missing Link: Technology, Investment, and Productivity - Power, Laura (The Review of Economics and Statistics, 1998)
This paper examines the relationship between productivity, investment, and plant age for over 14,000 plants in the U.S. manufacturing sector for the period of 1972 to 1988. Productivity patterns vary significantly due to plant heterogeneity. Initially productivity increases with respect to plant age, but then it decreases. Productivity and growth in productivity are found to be systematically correlated with plant size and industry. However, there is virtually no observable relationship between investment and productivity or productivity growth. Overall the results indicate that plant heterogeneity and fixed effects are more important determinants of observable productivity patterns than sunk costs or capital reallocation.